2007
DOI: 10.5194/acp-7-3571-2007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of using different ozone cross sections on ozone profile retrievals from Global Ozone Monitoring Experiment (GOME) ultraviolet measurements

Abstract: Abstract.We investigate the effect of using three different cross section data sets on ozone profile retrievals from Global Ozone Monitoring Experiment (GOME) ultraviolet measurements (289-307 nm, 326-337 nm). These include Bass-Paur, Brion, and GOME flight model cross sections (references below). Using different cross sections can significantly affect the retrievals, by up to 12 Dobson Units (DU, 1 DU=2.69×10 16 molecules cm −2 ) in total column ozone, up to 10 DU in tropospheric column ozone, and up to 100% … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 19 publications
3
50
1
Order By: Relevance
“…Original research by Liu et al (2007) found that the choice of the BDM ozone x-section would change GOME retrieved total ozone up to 12 %. The application of the BDM data for ozone retrieval also improved the spectral residuals of the fit to the satellite measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Original research by Liu et al (2007) found that the choice of the BDM ozone x-section would change GOME retrieved total ozone up to 12 %. The application of the BDM data for ozone retrieval also improved the spectral residuals of the fit to the satellite measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The OMI random noise errors reported in the level 1b radiance data are used to construct the measurement error covariance matrix. Ozone cross sections are from Brion-Daumont-Malicet (BDM) (Brion et al, 1993), which was recommended for use in ozone profile retrievals from UV measurements by Liu et al (2007) and Liu et al (2013). Despite these similarities, the two algorithms have many different implementation details, including state and a priori components, radiative transfer model calculations, and radiometric and wavelength calibration treatments.…”
Section: Ozone Monitoring Instrument (Omi) and Omi Ozone Algorithmsmentioning
confidence: 99%
“…HITRAN 2008 also contains polynomial coefficients (BP HITRAN ); however, a few corrections were made on the original BP data: air-vacuum wavelength conversion according to Edlen's equation (Edlen, 1966) and wavelength shift. Using original BMD data at four temperatures (218, 228, 243, and 295 K), Liu et al (2007) derived polynomial coefficients for temperature dependence for vacuum wavelength scale (BMD calc ), making possible the interpolation/extrapolation of the cross-sections to any given temperature. More details on the polynomial temperature parameterization of the cross-sections can be found, for example, in , and in our companion paper: Serdyuchenko et al (2014).…”
Section: Spectral Region 323-340 Nmmentioning
confidence: 99%